1997
DOI: 10.1046/j.1365-2133.1997.19542042.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma and granulomatosis

Abstract: Sarcoidosis or granulomatous reactions have rarely been reported in association with malignant melanoma (MM). We describe seven patients who presented with both granulomatous disease and MM, and discuss the physiopathological and prognostic significance of this association. In three patients, the granulomatosis was diagnosed as true sarcoidosis and in one patient, as tumour-associated granuloma. In three cases, designated here as atypical tumour-associated granulomatoses, the presence of clear-cut pulmonary gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…This distinction, however, has been taken not absolute by same authors [5], whereas others regard it as not helpful because ECGs negative for B cells are also observed in sarcoid reactions [22]. We found a few B cells especially within multiple and confluent ECGs even in sarcoidosis, probably intermingled by chance when the inflammation spread in B-cell areas of the affected lymph nodes.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…This distinction, however, has been taken not absolute by same authors [5], whereas others regard it as not helpful because ECGs negative for B cells are also observed in sarcoid reactions [22]. We found a few B cells especially within multiple and confluent ECGs even in sarcoidosis, probably intermingled by chance when the inflammation spread in B-cell areas of the affected lymph nodes.…”
Section: Discussioncontrasting
confidence: 52%
“…Because epithelioid cells are not selectively recognized by CD68 or any other current marker in routinely processed tissues, our findings concerning a well-working mAb to denatured human ACE [37] are important. High amounts of ACE in ECGs and epithelioid cells of sarcoidosis are known for long [23,38], and elevated serum levels of ACE have been clinically used as a criterion to distinguish sarcoidosis from sarcoid reactions [4,13,22]. ACE expression in ECGs other than sarcoidosis is controversial [23,38,39], although there are former reports on increased enzyme activities also in tuberculosis, leprosy, berylliosis, silicosis, and foreign body reaction [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulomatous reactions have rarely been reported in association with malignant melanoma. 9,10 In 1 of 7 cases reported by Robert et al, 9 and in the case reported by Tsunoda et al, 10 the granulomas were true tumor-associated reactions rather than sarcoidosis or suggestive of melanoma metastases. The sarcoid nodules disappeared with the treatment of the primary disease by surgery and chemotherapy in the case reported by Tsunoda et al 10 In addition, 2 cases of granulomatous reactions have been reported in the setting of targeted BRAF therapy.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to lymphoproliferative disorders, development of granulomatous reaction has been observed in lung and breast carcinoma (7), as well as in malignant melanoma (9). In the skin, both formation of granulomas representing a non-specific reaction pattern and true sarcoidosis -cutaneous or extracutaneous -have been rarely reported in association with Hodgkin's disease and non-Hodgkin extracutaneous lymphomas (10).…”
Section: Discussionmentioning
confidence: 99%